« Ici rien n’est vert. Ici rien n’est végétal. Ici rien n’est vivant » : l’hiver dans les témoignages des camps de concentration - Teklik, Joanna (Studia Romanica Posnaniensia, 2021)
For the prisoners of the concentration camps winter with its seasonal attributes as the icy cold or snow is more than a meteorogical phenomenon. The arrival of winter not only announces the annihilation of the prisonners, but also and perhaps above all their dashing and the unspeakable suffering to come out. In this paper we wish to study in the light of such authors as Robert Antelme, Charlotte Delbo, Primo Levi, David Rousset and Jorge Semprún how the hard weather conditions are able to redraw the space and the prisoners’Horizon of despair.